GABA spectra and remote distractor effect in progressive supranuclear palsy: A pilot study - Bonnet, Cecilia; Rusz, Jan; Hanuška, Jaromír; Dezortová, Monika; Jírů, Filip; Sieger, Tomáš; Jech, Robert; Klempíř, Jiří; Roth, Jan; Bezdíček, Ondřej; Serranová, Tereza; Dušek, Petr; et al. (Revue neurologique, 2017)
Disturbances of the gamma-aminobutyric-acid (GABA) system have been suspected of contributing to the pathophysiology of progressive supranuclear palsy (PSP). The ability to rapidly resolve competitive action decisions, such as shifting the gaze to one particular stimulus rather than another, can be predicted by the concentration of GABA in the region of the frontal cortex relevant to eye movements. For this reason, our study measured GABA levels in seven PSP patients and eight healthy controls, using proton magnetic resonance spectroscopy, and assessed the relationship of these measurements to the remote distractor effect (RDE), an eye-movement paradigm investigating competitive action decisions. No significant differences were found in either frontal-eye-field GABA levels or RDE between PSP patients and controls.
Keywords: Pilot Projects; Magnetic Resonance Imaging; Humans; lidé středního věku; Middle Aged; gamma-Aminobutyric Acid; pohyby očí; magnetická rezonanční tomografie; zraková pole; Magnetic Resonance Spectroscopy; sakadické oční pohyby; Eye Movements; světelná stimulace; zdraví dobrovolníci pro lékařské studie; mužské pohlaví; prefrontální mozková kůra; Supranuclear Palsy, Progressive; Photic Stimulation; okulomotorické svaly; Oculomotor Muscles; magnetická rezonanční spektroskopie; Saccades; ženské pohlaví; progresivní supranukleární obrna; Visual Fields; lidé; GABA; pilotní projekty; Aged; senioři; Male; Prefrontal Cortex; Healthy Volunteers; Female